Entanglement for two qubits induced by one-mode thermal field in the presence of the atomic coherence - E.K. Bashkirov; M.S. Mastyugin (Физика волновых процессов и радиотехнические системы, 2015)
In the prresent paper we have considered the influence of the initial atomic coherence on entanglement dynamics of two qubits one of which is trapped in a lossless cavity and interacts with single-mode thermal field, and the other one can be spatially moved freely outside the cavity. We have shown that the atomic coherence in the model under the consideration can be used for effective control on the degree of the entanglement of qubits.